Effect of the aggregates size on some properties of modified pervious concrete (Journal of University of Babylon for Engineering Sciences, 2017)
Pervious concrete is concrete mixture made from cement, coarse aggregates, water, little or no fines aggregate and in some cases admixtures. It has been considered a best management practice because of its ability to reduce storm water runoff and to initiate the filling of pollutants. Because the hydrologic  properties of pervious concrete has been the primary reason for its reappearance in roads. Pervious concrete strength and other properties mainly depend on aggregate size and proportion of the materials. This study focused on the effect of the aggregate size on the pervious concrete content of fiber and latex. The aim in this study of laboratory test was give rise progress the strength properties of pervious concrete during find out the maximum size of aggregate with incorporation fiber and latex. The test results indicate that strength and permeability of pervious concrete mixture was increase by the decreasing of maximum size aggregate.